Potret Kepemimpinan Transformatif di SD Muhammadiyah Nitikan Yogyakarta - Kholifah, Nisa Amalia; Setiawan, Farid; Almunawaroh, Nurullita; Wardani, Anesti Rohma; Ma’shum, Muhammad Azhar (Lembaga Yasin AlSys, 2022)
Education is an obligation for every human being to become a human being who has good quality. Education is also the main element in seeking knowledge, education is the basis or foundation in all aspects of science. The research method used in this paper is a qualitative approach. A qualitative research approach is used in finding, collecting, processing and analyzing the data that has been obtained in the study. with other elementary schools, so that in 2015 it became SD Muhammadiyah Nitikan, initially SD Muhammadiyah Nitikan was established which was headed by the school by the father of dish. Characteristics of Transformative Leadership, Barriers and Strategies of Principals in School Management, and SD Muhammadiyah Nitikan has achieved many achievements in the arts in South Korea and sports until it was obtained internationally and in that SD Muhammadiyah has various excellent programs of course this will make SD Muhammadiyah and the Principal proud Of course, in doing this it is proven that it can solve it well.